EFEKTIVITAS PEMANFAATAN BANTUAN DANA PEMULIHAN EKONOMI NASIONAL (PEN) OLEH DINAS PUPR KABUPATEN GORONTALO : (Studi Kasus: Di Desa Buhu Kecamatan Tibawa Kabupaten Gorontalo) - Rahayu Liputo, Sri; Nggilu, Rukiyah; Kadir, Jusrin (STISIPOL Mujahidin Buol, 2023)
This research aims to determine the effectiveness of utilizing PEN funding assistance. The research method used is descriptive qualitative. The results of the research concluded that, the absorption of the PEN budget for village road construction has not been optimal, this can be seen from the insufficient budget to complete the village road construction project. The human resources involved in the village road construction project have not fully utilized or involved the Buhu Village community. The implementation of road construction projects was not completed on time. This can be seen from the mismatch in the planned time with the fact that to date the road construction project has not been completed